Work Environment on Employee Performance - Fahriz, Firman (Jurnal Bisnis Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of the work environment and work discipline on employee performance. The type of research used is a narrative literature review of 3 (three) articles that discuss the influence of the work environment on employee performance in a company with the aim of identifying and summarizing previously published articles without any criticism for the articles being reviewed. From the three articles it is agreed that the results of the study state that the Work Environment and Work Discipline have a significant effect individually and jointly have a significant effect on Employee Performance. A comfortable work environment and a high level of discipline will improve employee performance. The work environment also has a positive and significant influence on work productivity, meaning that if the work environment is improved, the better it can increase work productivity.